Joint health and treatment modalities in Nordic patients with moderate haemophilia A and B – The MoHem study. Issue 5 (27th July 2020) - Måseide, Ragnhild J.; Berntorp, Erik; Astermark, Jan; Olsson, Anna; Bruzelius, Maria; Frisk, Tony; Nummi, Vuokko; Lassila, Riitta; Tjønnfjord, Geir E.; Holme, Pål A.
Abstract: Introduction: The prevalence of arthropathy in moderate haemophilia A (MHA) and B (MHB) is not well known. Aim: We evaluated joint health in Nordic patients in relation to their treatment modality. Methods: A cross‐sectional, multicentre study covering MHA and MHB in Sweden, Finland and Norway. Arthropathy was evaluated by ultrasound (HEAD‐US) and Haemophilia Joint Health Score (HJHS). Results: We report on 145 patients: median age 28 years (IQR 13‐52) and 61% MHA. Baseline factor VIII/factor IX activity (FVIII/FIX:C) was 2 IU/dL (median) (IQR 2‐4): lower for MHB (2 IU/dL, IQR 1‐2) than MHA (3 IU/dL, IQR 2‐4) ( P < .01). Eighty‐five per cent of MHA and 73% MHB had a history of haemarthrosis ( P = .07). Age at first joint bleed was lower for MHA (5 years [median], IQR 3‐7) than MHB (7 years, IQR 5‐12) ( P = .01). Thirty‐eight per cent received prophylaxis, started at median 10 years of age (IQR 4‐24). Median joint bleeds and serious other bleeds during the last 12 months were both zero (IQR 0‐1). Total HEAD‐US captured 0/48 points (median) (IQR 0‐2) and HJHS 4/120 points (IQR 1‐10) with strong correlation between them ( r = .72). FVIII/FIX:C ≤ 3 IU/dL was associated with higher HJHS ( P = .04). Fifteen per cent had undergone orthopaedic surgery. Conclusion: The current joint health in Nordic moderate haemophilia patients was rather good, but a subgroup had severe arthropathy. FVIII/FIX:C ≤ 3 IU/dL and MHA were associated with a more severe bleeding phenotype. We suggest primary prophylaxis to all patients with FVIII/FIX:C ≤ 3 IU/dL.